Strategic Role of Human Resource Management in the Company: Strategic Role of Human Resource Management in the Company - Noor Muhammadi; Noor Permadi (Jurnal Mantik, 2020)
This study aims to determine the indicators of success in resource management in providing compensation to improve performance and employee development to increase skills in carrying out tasks within the company. Human resource management also concerns the design and implementation of planning systems, employee arrangement, employee development, career management, performance evaluation, employee compensation and good employment relations. Human resource management involves all management decisions and practices that directly affect human resources. Resources relate to everything that is a company asset to achieve its goals. Resources owned by the company can be categorized into four types of resources, such as financial, physical, human and technological capabilities. Financial resources are one of the important elements in order to form a company that is progressive and continues to grow because it relates to stocks which are the main capital in building a company and developing and continuing the company. Physical resources are resources related to physically supporting the establishment of a company such as its supporting tools. Human resources are a central and important sector in order to achieve goals in a company, because with the ability of workers' skills and the quality of human resources it can move the company properly and correctly. Technological capability is also an important supporting element in moving the company, because the complete technology and technological sophistication will facilitate the running of a company. Of the four sources, the most important aspect is humans, because humans are the most important mover in a company. Whether the company progresses or not depends on the management of human resources that can be done within a company or by a particular department.